2022
DOI: 10.1101/2022.11.11.516204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Core Defense Hotspots withinPseudomonas aeruginosaare a consistent and rich source of anti-phage defense systems

Abstract: Bacteria use a diverse arsenal of anti-phage immune systems, including CRISPR-Cas and restriction enzymes. Identifying the full defense repertoire of a given species is still challenging, however. Here, we developed a computational tool to broadly identify anti-phage systems, which was applied to >180,000 genomes available on NCBI, revealingPseudomonas aeruginosato possess the most diverse anti-phage arsenal of any species with >200 sequenced genomes. Using network analysis to identify the common neighbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…In contrast, hotspot #37 was highly occupied, with diverse defense systems present in almost all genomes in which it was detected. This position seems to represent a dedicated defense hotspot that may play a role in promoting defense system diversity within the E. coli pan-genome, as was also observed in strains of P. aeruginosa [39].…”
Section: Plos Geneticsmentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, hotspot #37 was highly occupied, with diverse defense systems present in almost all genomes in which it was detected. This position seems to represent a dedicated defense hotspot that may play a role in promoting defense system diversity within the E. coli pan-genome, as was also observed in strains of P. aeruginosa [39].…”
Section: Plos Geneticsmentioning
confidence: 53%
“…While in some cases hotspot #37 contained prophages, P4-type phage satellites or IMEs, the majority (68.0%) of mobile islands carrying defense systems at this hotspot did not have any detectable MGEs, although many contained integrase or recombinase genes (Fig 6 and S2 Table). Notably, a recent study showed that Pseudomonas aeruginosa genomes encode two highly diverse hotspots that seem to be similarly dedicated to carrying defense systems, with some cases showing no identifiable modes of mobilization [39].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In addition, these MGE tend to integrate at preferential locations in bacterial genomes, known as integration hotspots. Therefore, systematic mapping of integration hotspots and careful analyses of their gene content is becoming a valuable strategy for the discovery of the full repertoire of bacterial defence systems [40][41][42][43] . We now understand that bacteria encode many more defence systems than previously thought, and that individual bacterial genomes typically contain multiple defences.…”
Section: Discussionmentioning
confidence: 99%
“…Computational prediction of the presence or absence of various defense systems in ECOR strains used in the PhAGENT screen. Predictions were generated using the ISLAND software suite 57 .…”
Section: Supplementary Figure 1 Phage-host Combinations Included In P...mentioning
confidence: 99%